The effect of free-hit rule changes on match variables and patterns of play in international standard women's field hockey - Tromp, M.; Holmes, L. (International Journal of Performance Analysis in Sport, 2011)
Rule changes are a common feature in sports today and objective assessments are required to ascertain the impact of such changes. The current project sought to investigate the intention of the latest rule change in field hockey that was introduced in 2009 by the International Hockey Federation (FIH) - the use of a "self-pass" as a legitimate method of taking a free hit, and changes to the procedures for taking free hits within the 25 yard area. Twenty-eight (n=28) international women's field hockey games were analysed for changes in time-variables from repossession to final outcome, along with methods and areas of repossessions and circle penetrations. Results indicate that the intention of the self-pass rule was met by significantly decreasing the average amount of time taken to engage in free hits (8.0 ± 0.9s in 2008 to 4.6 ± 0.3s in 2009), reducing the disruption of flow to the game. A significant difference was found in the method of circle penetrations, with most penetrations occurring by dribbling (33% in 2008, 57% in 2009). A significant decrease in time taken from repossession in the defensive 25 left and defensive left indicates an increase in the intensity of the game, emphasising the importance of aerobic capacity of participants.